New trends in EU’s economic relations with China - Chen Xin (Global Economic Observer, 2013)
EU’s economic relations with China in 2012 may be sum up in 4 points. Firstly, EU tried to seek Chinese support in order to facilitate the efforts of stabilizing the market confidence and gain some time for seeking solutions for the European Sovereign Debt Crisis. Secondly, EU tried to expand exports to China, but the effects of its measures are limited. Thirdly, EU strengthened the market defence actions to protect European market, which led to harsh trade disputes between EU and China. Fourthly, EU accelerated the implementation of Global FTA Strategy with the aim to promote exports and to set up new standards in world trade, which could weaken the Chinese competitive advantages. EU’s actions could be understood as a kind of pragmatism, and the contradictions of the actions exposed the lack of vision on its strategy for China and its vague position on EU-China Comprehensive Strategic Partnership. There is an urgency on behalf of the EU to clarify its strategic position toward China, otherwise it would be harmed the continuity of the EU-China Comprehensive Strategic Partnership.